(untitled) (Research, Society and Development, 2020)
It analyzes works of the History of Professional Education in Brazil, with emphasis on those that deal with Apprentice Schools created in the capitals of Brazilian states in 1909. It seeks to understand the lines of interpretation prevailing in this field of historiography, ranging from classic works by Fernando de Azevedo, A Cultura Brasileira, 1950, and História do Ensino Industrial no Brasil, launched in 1961 by engineer Celso S. da Fonseca, until the recent dissertations and theses presented in several graduate courses in Brazil. It observes the diversity of the field of History of Professional Education in Brazil, considering the profile of those who write this History and the different possible lines of interpretation. It concludes that the field of History of Professional Education in Brazil follows the paradigm changes experienced by Historiography, with emphasis on the end of the great narratives and the adoption of new themes and approaches, such as the discussions about power relations and uses of spaces, based on Foucauldian concepts.